Effectiveness of Tocilizumab in the Treatment of Fasciitis with Eosinophilia: Two Case Reports - Pinheiro, Maria Guiomar (2021)
Fasciitis with eosinophilia (FE) is a rare connective tissue disease. Due to its rarity, large-scale studies are lacking, which makes its treatment challenging. Systemic corticosteroids (SCSs) are the cornerstone of treatment; however, additional immunosuppressive drugs (ISDs) are frequently necessary (usually methotrexate). We report 2 patients, for whom an SCS and methotrexate were not a viable long-term option. In the first case, we were unable to taper the SCS dose without symptom relapse, the patient showed only a partial response to methotrexate and presented side effects. The second case never fully responded to the SCS and methotrexate and demonstrated serious SCS adverse effects. Both patients were started on tocilizumab with extremely favourable results, making this drug a potential therapeutic weapon for these patients. Learning points: The treatment of FE is challenging and mainly based on retrospective reviews, open-label trials and case reports, all of which included a small number of patients.Currently, systemic corticosteroids are the mainstay of treatment; however, other ISDs are frequently necessary.Cases showing a favourable clinical response to tocilizumab have recently been described in patients with corticosteroid-refractory disease, suggesting that this drug may potentially become a therapeutic weapon for these patients.